3-BOYUTLU MİNKOWSKİ UZAYDA RİBBON ÇATIYA GÖRE FOKAL EĞRİLER - ÜSTÜNDAĞ, UĞUR (Fırat Üniveristesi, 2022)
Minkowski uzayında eğriler teorisinde farklı çatılara göre birçok çalışma yapılmıştır. Birçok bilim adamı bu teoride Frenet çatı, Bishop çatı, Adapted çatı, gibi çatıları çalışmıştır. Bu çatılar eğriler ile ilgili karakterizasyonlarda bize yardımcı olur. Bu tezin amacı, Minkowski uzayında ribbon çatıyı göre fokal eğrileri araştırmaktır. Bu amaç doğrultusunda, ilk önce ribbon çatı tanımlandı. Daha sonra bu çatıya bağlı olarak space-like ve time-like fokal eğriler verildi ve çeşitli karakterizasonlar elde edildi.

Many studies have been done according to different frames of the theory of curves in Minkowski Space. Many scientists have studied frames such as the Frenet, Bishop, and Adapted frames in this theory. This frame helps us in the characterization of curves. The goal of this thesis, the focal curves according to the Ribbon frame in 3-dimensional Minkowski space to be investigated. In line with this purpose, the ribbon roof was first defined. Then, depending on this frame, space-like and time-like focal curves were given and various characterizations were obtained.
Focal curves according to the ribbon frame in 3-dimensional minkowski space
Keywords: Matematik